Apakah Ukuran, Profitabilitas, dan Praktik Manajemen Laba Memengaruhi Tingkat Pelaksanaan dan Pelaporan Islamic Social Reporting Pada Perbankan Syariah Di Indonesia? - Iwan Setiawan; Haris Faulid Asnawi; Hafiez Sofyani (Jurnal Dinamika Akuntansi dan Bisnis, 2016)
This study aims to examine the effect of size, profitability, and earnings management on implementation and disclosure of Islamic Social Reporting in Islamic banks in Indonesia. The samples are Indonesian General Islamic Banks (Bank Umum Syariah) which published an annual report within the past three years from 2009 to 2013. Measurement of Islamic Social Reporting was perfomed with reference to the research Haniffa (2002). The hypothesis testing employs multiple regression analysis techniques. The results of this study reveal that the size of banks as measured by total assets has positive effect on the level of implementation and disclosure of Islamic Social Reporting by Islamic banks. However, profitability as measured by return on eearnings (ROE) and earnings management as measured by Healy model (1996) do not show the effect on the level of implementation and disclosure of Islamic Social Reporting by Islamic banks. For more detail descriptions of this study results are presented in discussion section.